2010
DOI: 10.1016/j.foodchem.2009.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and thermal properties of β-galactosidase enzymes produced by artisanal yoghurt cultures

Abstract: , respectively. Moreover, thermodynamic (DG, DS, DH) and kinetic constants (K m and V max ) were determined and effects of metal ions were investigated. As a result, these enzymes could be considered as potential candidates for lactose hydrolysis of milk and milk products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 25 publications
4
32
0
2
Order By: Relevance
“…However, our study was lower than the values reported by Fuquay et al (2011);Batista et al (2008); Tamime and Robinson (2007) who noticed that a greater consumption of lactose was metabolized up to ~20-30% by bacterial of yogurt culture through 2 h of incubation in fermented milk. In contrast, Ustok et al (2010); Kreft et al (2001) using L. delbrueckii ssp. bulgaricus ATCC 11842 and S. thermophilus95/2 pure strains, indicated up to 60% of lactose hydrolyzed at the Linko et al (1998) reported that only about 45-68% of the lactose in the medium was utilized by S. thermophilus11F under the experimental conditions used.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, our study was lower than the values reported by Fuquay et al (2011);Batista et al (2008); Tamime and Robinson (2007) who noticed that a greater consumption of lactose was metabolized up to ~20-30% by bacterial of yogurt culture through 2 h of incubation in fermented milk. In contrast, Ustok et al (2010); Kreft et al (2001) using L. delbrueckii ssp. bulgaricus ATCC 11842 and S. thermophilus95/2 pure strains, indicated up to 60% of lactose hydrolyzed at the Linko et al (1998) reported that only about 45-68% of the lactose in the medium was utilized by S. thermophilus11F under the experimental conditions used.…”
Section: Resultsmentioning
confidence: 95%
“…These observations agree with Wang et al (1996) who reported that the activity of β-galactosidase depends on pH; it decreases rapidly at lower pH values. Also, Gueimonde et al (2002);Carević et al (2015); Ustok et al (2010) demonstrated that Lactobacillus acidophilus, L. delbrueckii ssp. bulgaricus, and S. thermophilus displayed significantly higher levels (P< 0.05) of β-galactosidase activity at pH 6.3 (activity over 90% of maximum) with an optimum at pH 6.0 -7.0 and then lose in activity as the pH decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of lysozyme the concentration of lysozyme used for the cell disruption was standardized and use of 10 mg of lysozyme per ml of the cell suspension was found to be suitable for cell disruption. In some other studies, 22 mg of lysozyme per ml of the cell suspension was used for cell disruption Ustok et al 2010). In glass beads and sonication, the time required to disrupt the cells was standardized.…”
Section: Discussionmentioning
confidence: 99%
“…A partir da Tabela 1 podemos observar que com o aumento da temperatura ocorre um leve decréscimo nos valores de energia livre de Gibbs (∆G*). Todos os valores de ∆G* estão na ordem de magnitude esperada para desnaturação proteica 9 . Os valores ∆H* e ∆S* (Tabela 1) obtidos no presente estudo, também estão de acordo com o esperado para enzimas desnaturadas pelo calor.…”
Section: Bbr -Biochemistry and Biotechnology Reports -Issn 2316-5200 unclassified